Consumption Patterns of Indebted Households: Unravelling the Relevance of Fiscal Policy - António Afonso; Eduardo de Sá Fortes Leit\~ao Rodrigues (Center for Economic Studies and ifo Institute (CESifo), 2023)
We have investigated the influence of fiscal instruments, notably taxes on income and government spending, on household consumption in two different samples and two measures of household debt to provide a comprehensive analysis of the topic. We used dynamic panel models and the GMM approach for 32 advanced and emerging countries from 1995 to 2019. Our findings suggest that fiscal impulses increase private consumption, but when households are highly indebted, patterns change, and increased government spending or reduced taxes, in the presence of high indebtedness, actually discourage household consumption compared to the baseline (lower debt) group.
Keywords: C32; E58; E62; E63; 330; household consumption; household debt; fiscal policy; panel data